(untitled) (Journal of Geography and Environmental Management, 2017)
One of the main indicators characterizing the economic development of countries and regions, is quality of life. With the integration of the Republic of Kazakhstan into the world economy the interest to this problem increases. Indicators of quality of life are intended to reflect the level of development of socio-economic processes in the country. The article deals with the evolution of «the quality of life» category and research approaches to the definition. Quality of life is studied in many fields of science, since the 1960 years. At the same time today does not exist any established regulatory definition of this category. In numerous researchers devoted to the study of quality of life, authors represented their interpretation of quality of life, depending on the object and the direction of research. Based on the analysis of references on quality of life tables are made up. In tables reflected the main theoretical approaches to the study of quality of life. It emphasizes the interdisciplinary nature of research of quality of life, an analysis of different approaches to the category of the quality of life, including geographical aspect of the definition of quality of life. The role of the geographic approach is identify territorial differences quality of life. Based on researchers the author’sgave their definition of quality of life in terms of geography.